The invasion of America : Indians, colonialism, and the cant of conquest - Jennings, Francis, 1918-2000. 4 0 16; 5 (Chapel Hill : Published for the Institute of Early American History and Culture by the University of North Carolina Press, 1975)
The cultural devastation of Atlantic coastal Indian tribes by European civilization, particularly New England Puritans, and the creation of an ideology to justify the cruelty are studied.
Myths of the Marchlands -- The heathen for inheritance, and the earth for possession.
Includes index.
Bibliography: p. 337-354.
Keywords: 2 -- 0; 6; Government relations;Government relations. -- Indians of North America;Indians of North America;Iroquois Indians -- New England. -- To 1789.20; History -- New England -- Colonial period, ca. 1600-1775.20; 2